Cereal Circular RNAs (circRNAs): An Overview of the Computational Resources for Identification and Analysis - Vaschetto, Luis; Litholdo Jr., Celso Gaspar; Sendín, Lorena Noelia; Terenti Romero, Claudia Mabel; Filippone, Maria Paula (2022)
Circular RNAs (circRNAs) are a widespread class of endogenous noncoding RNAs and they have been studied in the past few years, implying important biological functions in all kingdoms of life. Recently, circRNAs have been identified in many plant species, including cereal crops, showing differential expression during stress response and developmental programs, which suggests their role in these process. In the following years, it is expected that insights into the functional roles of circRNAs can be used by cereal scientists and molecular breeders with the aim to develop new strategies for crop improvement. Here, we briefly outline the current knowledge about circRNAs in plants and we also outline available computational resources for their validation and analysis in cereal species.